Design, development and manufacture of a small electric motor dynamometer - Hong Thong Duc; Truong Phat Tan; Pham Minh Quang; Ho Hoa Nam; Le Hoang Minh Do; Vu Thang Viet (FME Transactions)
Studying electric vehicle performance, operating range, and control algorithms is still limited in developing countries because it requires specialized equipment, while electric vehicles are increasingly widely used, such as electric cars, electric motorbikes, electric bicycles, etc. This paper introduces the design and manufacture of a small electric motor dynamometer, especially the in-wheel motor. Based on the performance of electric motors and the alternator characteristics, the chain drive was cautiously analyzed and designed to investigate different electric motor speed characteristics over their entire operating range. Especially in this study, the chain drive has three stages with transmission ratios of 1/4, 1/3, and 1/2.5. Besides, a controller that can automatically adjust the electric load level to determine various motor characteristics under constant load and throttle settings is also designed to control the dynamometer and collect essential data. Furthermore, the graphic user interface is built to operate the dynamometer quickly and flexibly. With a flexible transmission ratio and a comprehensive algorithm control, the dynamometer can investigate various characteristics of electric motors used for popular motorbikes and bicycles with power up to 3000W. The designed dynamometer not only has a compact design, stable operation, and affordable price but is also easy to assemble, operate, and maintain. These findings can be applied to develop the dynamometer to investigate the performances of the electric motor and its auxiliary system, serving the research and development process of electric motorbikes used in developing countries today.